Exploring the antecedents and consequences of epistemic emotions. (October 2019) - Chevrier, Marianne; Muis, Krista R.; Trevors, Gregory J.; Pekrun, Reinhard; Sinatra, Gale M.
Abstract: Across two studies, we evaluated a model that proposed relations between epistemic cognition, epistemic emotions, self-regulatory strategies, and learning of complex contradictory content. For Study 1, to capture epistemic cognition, epistemic emotions, and self-regulatory strategies, 114 undergraduate students thought out loud while reading conflicting texts about climate change. Protocol analysis revealed that epistemic aims, epistemic congruity, and appraisals of novelty and complexity of information served as antecedents to epistemic emotions. State-transition analyses revealed that curiosity increased the likelihood of metacognitive self-regulation, and that surprise decreased the likelihood of rehearsal and increased the likelihood of critical thinking. For Study 2, participants reported epistemic beliefs, read contradictory texts about climate change, reported emotions experienced while reading, and completed a knowledge assessment task. Path analyses revealed full mediation between epistemic beliefs, epistemic emotions, learning strategies and learning achievement. More constructivist beliefs about the complexity, uncertainty and justification of knowledge predicted more curiosity, less surprise, and less boredom. Curiosity, in turn, predicted critical thinking, knowledge elaboration and rehearsal strategies. Finally, critical thinking and rehearsal positively predicted learning achievement. Implications for research on epistemic cognition, epistemic emotions, and self-regulated learning are discussed. Highlights: Epistemic emotions mediated relations between epistemic beliefs and self-regulated learning. Epistemic emotions antecedents included epistemic aims, epistemic congruity, information novelty and complexity. More constructivist epistemic beliefs predicted less negative epistemic emotions. Curiosity increased the likelihood of metacognitive self-regulation. Surprise decreased the likelihood of rehearsal and increased the likelihood of critical thinking.